PENGARUH PENGENALAN LAPANGAN PERSEKOLAHAN DAN DUKUNGAN KELUARGA TERHADAP MINAT MENJADI GURU PADA MAHASISWA PIPS ANGKATAN 2021 UNIVERSITAS JAMBI - Resnawati; Muhammad Arif Liputo; Sahara (LPPM STAI Muhammadiyah Probolinggo, 2025)
The School Field Introduction Program (Pengenalan Lapangan Persekolahan or PLP) serves as a crucial practical experience for education students in preparing to become professional teachers. However, the interest in becoming a teacher is not always rooted in intrinsic motivation; it is often influenced by external factors such as family support. This study aims to examine the influence of PLP and family support on the interest in becoming a teacher among 2021 cohort students of the Social Science Education Program (PIPS) at Universitas Jambi, both partially and simultaneously. This quantitative research employed an ex post facto method. The sample consisted of 73 students selected using proportionate stratified random sampling, with data collected through an online questionnaire via Google Forms. The data were analyzed using descriptive and inferential statistical techniques. The results revealed that partially, PLP had a positive and significant effect on the interest in becoming a teacher (tvalue = 3.818; sig = 0.002), and family support also had a positive and significant effect (tvalue = 7.031; sig = 0.000). Simultaneously, PLP and family support significantly influenced students' interest in becoming teachers (Fvalue = 25.275; sig = 0.000), with a coefficient of determination (R²) of 61.9%. These findings are expected to provide insights for educational institutions in designing strategies to enhance the quality of PLP and foster collaboration with students' families. This study also opens further discussion on how other external factors, such as the social environment and media influence, contribute to shaping students' perceptions and interest in the teaching profession amid the challenges of educational modernization.